Evaluating the sustainability of China's power generation industry based on a matter-element extension model. (April 2021) - Wang, Yongli; Yang, Jiale; Zhou, Minhan; Zhang, Danyang; Song, Fuhao; Dong, Fugui; Zhu, Jinrong; Liu, Lin
Abstract: Considering the urgency of the clean energy transformation, this study evaluates and analyzes the sustainability of five power generation subsectors in China. First, the sustainability evaluation index system is established, comprehensively considering economic, environmental, technological, and social dimensions. Secondly, the sustainability evaluation model is established via the improved matter-element extension method. The results of the analysis show that the sustainability of the five power generation subsectors in descending order are nuclear power, wind power, photovoltaic power, hydropower, thermal power. Finally, policy suggestions for the power generation industry are put forward. Highlights: The evaluation index system of power generation industry can comprehensively reflect the sustainability situation. Based on AHP-entropy weight method, an improved matter-element extension evaluation model is constructed. The sustainability of five power generation industries in China was evaluated. Development suggestions are put forward for the future power structure optimization in China.